Pemetaan Tren Penelitian Menggunakan Model 4D Pada Penelitian Pendidikan IPA - Nisa Hidayatullah; Satutik Rahayu; I Putu Artayasa (Action Research Journal, 2025)
The 4D development model has been widely studied, but the grouping of research results regarding the 4D development model is still less researched, this study aims to analyze the research trends of the 4D model development in science education research, including the types of products developed, the focus of the study, research methodology, and the development of the number of publications. This research method is descriptive analytical, which aims to understand and describe research trends in the development of using the 4D model in science learning. The data used in this study were obtained from information sources indexed by Google Scholar using analysis tools such as Publish or Perish and Dimension.ai. To conduct a search on Google Scholar, keywords related to research trends on the development of using the 4D model in science learning have been used. There has been a lot of development research in the field of science learning in Indonesia with a total of 3757 articles in the last 10 years. The development research that is currently being carried out is technology-based media and assessment instruments, both in the form of Android applications and PC or internet-based. With the development models used are diverse and the most widely used is 4D. Further development research is expected to start using technological developments and communication advances such as the development of hypermedia, augmented reality, and virtual reality